ANALYSIS OF ERRORS IN THE GOOD AND CORRECT USE OF INDONESIAN IN NOTIFICATION LETTER - Ertinawati, Yuni; Nabilia Ly, Zahra; Fuziyanti, Lorena; Rahmani, Agni Dwi; Atmadja, Muhammad Dicka Setya (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Errors in using Indonesian in notification letters often result in confusion and misunderstanding among recipients. Apart from that, spelling errors and inappropriate use of terms were also found, which could damage the sender's credibility. This research aims to describe, correct and analyze forms of language errors in the form of errors in the use of Indonesian contained in notification letters issued by the Poltekkes Kemenkes Tasikmalaya. Types of errors are studied through the use of Indonesian spelling based on the General Guidelines for Indonesian Spelling and Standard Vocabulary (KBBI). Various errors were found, (1) use of capital letters, (2) non-standard word writing, (3) incorrect acronyms, (4) punctuation errors, (5) and typing errors. This error is caused by the author's lack of understanding of Enhanced Spelling rules (EYD) and low interest in reading. The impact of this error can interfere with understanding the message and image of the institution. Therefore, it is important to improve understanding and skills in the Indonesian language among official letter writers.